Analisis Manajemen Sarana dan Sarana pada SMAS Pertiwi Medan - Sani Susanti; Efridayanti Efridayanti; Imel Tamara Ambarita; Nurwidia Kasih; Samuel Kristian Putra Hasibuan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
In the field of education or within the scope of school facilities and infrastructure management is an important factor in creating an ideal and effective learning environment for students at school. With the planning, procurement, organization, use, and elimination of educational facilities and infrastructure, all these aspects are interrelated and affect each other. This procedure needs to be done carefully and precisely in order to create efficient and effective conditions within the school environment. Facilities and infrastructure in its implementation will be a good resource for students and teachers if managed properly will have a positive impact on both parties to create an attractive learning environment and increase student success. This study aims to determine how the management of facilities and infrastructure carried out by the school in SMAS Pertiwi Medan, whether the facilities and infrastructure in the school meet the criteria for good management of educational facilities and infrastructure. The method in this study uses qualitative research methods. From the results of the study, researchers found that in the management of facilities and infrastructure at SMAS Pertiwi Medan school has been adequate to be categorized as a school that has effective and good management of facilities and infrastructure for students in the school.This can be seen from the results of observations made by researchers in terms of existing buildings in the school, complete classrooms, libraries, laboratories, sports halls, and can be seen in areas outside the school such as vehicle parking facilities and also school canteens, this can increase student learning motivation by having adequate facilities and infrastructure for learning in SMAS Pertiwi Medan.